Evaluation of stewarts model for acid-base balance in patients with diabetic ketoacidosis. - Paiker, Janice Errela (My University, 2014)
The importance of the regulation of pH in body fluids is well established, and measurements in this regard are made routinely in a number of clinical situations. In order to fully appreciate the nature of an acid-base disorder, a precise understanding of the determinants of hydrogen ion concentration is required.Unfortunately, current physiological teaching tends to be over simplified, and does not incorporate fundamental physico-chemical aspects of aqueous solutions, which are essential far a thorough understanding of the subject. This deficiency was addressed by Stewart who analysed complex aqueous solutions and proposed a model based on sound chemical theory and a number of simplifying assumptions.The model accounts for the simultaneous influences of the important variables affecting hydrogen ion concentration, rather than using a single equation (Henderson Hasselbalch for C02) to explain acid base equilibria. Stewart's model differentiates between dependant variables such as hydrogen, hydroxyl and bicarbonate ions, and independent (controllable) variables namely the partial pressure of carbon dioxide pC 02, the concentration of net ionic charge of strong electrolytes known as the strong ion difference SID , and total weak acids Atot. The model goes on to predict the relationships between all these variables such that any dependant variable can be calculated uniqutily ib r measured or postulated values of the three independent variables. To establish whether this model could account for all factors influencing acid-base changes in a clinical setting it was decided to study patients with Diabetic Ketoacidosis, as the biochemistry of this disorder is well known. Arterial and venous blood was collected from twenty patients with the diagnosis of Diabetic Ketoacidosis as part of their routine management. Hydrogen ion concentrations and the concentrations of the independent variables were measured, and the results of measured hydrogen concentrations and predicted hydrogen ion concentrations based on Stewart’s model using measured independent variables were compared. Extreme discrepancies were found between the measured hydrogen ion concentrations and those calculated using Stewart's model in this patient group. As the model is able to accurately predict hydrogen ion concentrations from simple solutions, the reasons for the discrepancies in complex biological solutions remain uncertain. The two major areas which may account for these changes are accuracy of measurement and protein chemistry. In conclusion, the sound chemical and thermodynamic basis of Stewart’s model makes it likely to be correct in principle, however further research is essential to elucidate the specific causes of discrepancy between theory and measurement in the clinical setting.